Changes in plant species diversity as affected by shading conditions and continuous agricultural practices in kiwifruit orchards - Triantafyllidis, Vassilios; Zotos, Anastasios; Kosma, Chariklia; Kehayias, George; Pittaras, Antonios; Drougas, Panagiotis (Emirates Journal of Food and Agriculture, 2022)
The environmental impact of commercial Mediterranean kiwifruit ’Hayward’ orchards was assessed after ten years of continuous cultivation. Species diversity seems to be influenced both by the subcanopy photosynthetically active radiation (PAR) budget, and the usual agricultural practices in conventional orchards. The largest reduction of species diversity ( 64%) was observed in kiwifruit orchards with pergola canopy structure followed by that in T-bar canopy structure ( 34%) in comparison with new installed kiwifruit orchards. In excessive shading conditions and particularly in well irrigated kiwifruit orchards with the synergistic effect of the above variables, the highest reduction of plant species has occurred. The continuous herbicides application and the soil compaction are strongly correlated with the reduction of taxa, while the long-term agricultural practices, such as inorganic fertilizers and Cu-fungicides application, have a negative impact on plant species diversity in kiwifruit orchards.